PTP1B inhibitory flavonols from Orthosiphon stamineus Benth - Hung, Nguyen Phi; Thuan, Hoang Duc; Nghi, Do Huu; Trung, Vu Quoc; Long, Pham Quoc (Vietnam Journal of Chemistry, 2017)
From the alcoholic extract of the aerial parts of Orthosiphon stamineus Benth., three flavonols have been isolated. Their chemical structures were elucidated to be 5,7,3’,4’-tetramethylquercetin (1), 3’-hydroxy-3,5,7,4’-tetramethoxyflavone (2), and 3,5-dihydroxy-7,3',4'-trimethoxyflavone (3), by combining spectroscopic data and physicochemical data analyses (including IR, UV, NMR and MS). Compounds 1-3 exhibited potential PTP1B inhibitory activities with IC50 values of 8.92±0.72, 22.25±1.70, and 52.64±4.12 µM, respectively. The positive control, ursolic acid, showed an IC50 value of 3.42±0.97 µM in this assay. Keywords. Orthosiphon stamineus Benth., PTP1B inhibitor, flavonol, Cat’s whiskers, flavonoid.